Kapasitas Dinas Perindustrian dan Perdagangan Kabupaten Deli Serdang dalam Mengelola Pasar Rakyat Tanjung Morawa - Popi Damayanti; Muhammad Imanuddin Kandias Saraan (Universitas 17 Agustus 1945 Semarang, Indonesia, 2025)
Managing public markets is one form of government service aimed at improving community competitiveness, as regulated in the Republic of Indonesia Law No. 7 of 2014 concerning Trade and the Minister of Home Affairs Regulation No. 20 of 2012 concerning the Management and Empowerment of Traditional Markets. Public markets play a vital role as local economic drivers that support community livelihoods. According to Utamanews.com (2022), Tanjung Morawa Public Market, located on Jalan Gerilya, Tanjung Morawa District, was rated by business actors as the poorest-performing public market in Deli Serdang Regency. This study aims to describe the capacity of the Department of Industry and Trade (Disperindag) of Deli Serdang Regency in managing the Tanjung Morawa Public Market. The research uses a descriptive qualitative method with data collected through observation, interviews, and documentation. The analysis is based on Horton et al.’s (2003) organizational capacity indicators, including human resources, infrastructure, technology, budgeting, and organizational activities. The findings reveal that Disperindag has not yet reached optimal capacity in market management, as evidenced by weak human resources, poorly maintained infrastructure, lack of technological application such as REPATONIK, limited budget allocation, and ineffective organizational activities in maintaining cleanliness and regulating street vendors around the market.